The Prevalence of Yersinia enterocolitica Species in the Flow of Butchering - Ciceronis Cumpanasoiu; Cristian Emil Cumpanasoiu; Emil Tirziu; Radu Trif (Scientific Papers Animal Science and Biotechnologies, 2023)
During the experimental stages, the researches aimed to establish the prevalence of Y. enterocolitica bacteria on swine, in the butchering flow. The experiments developed on a large number of test specimens (800), sampled starting with the moment of animals receiving and until the final product was obtained. For isolation and identification there were used a modified method, proposed by The International Organization for Standardization, and CIN and SSDC isolating cultures as well. Following the effectuated researches, in accordance with the international ones, we can conclude that, in the present, the butchering process allows the strict observance of the hygiene and disinfection conditions with the purpose of limiting the dispersion of Yersinia enterocolitica, which favors the phenomenon of inter-contamination.